2024
DOI: 10.5132/eec.2015.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity identification and evaluation of a refinery wastewater from Brazil (Phase I)

Abstract: Petroleum refineries generate a large amount of effluents, which if released without appropriate treatment can cause chronic effects to organisms. Most studies show that many contaminants can be responsible for the toxicity, among them ammonia, sulfide, cyanide, phenol and hydrocarbons. The present study evaluated the cause of the chronic toxicity of a refinery wastewater from Brazil using the organism Ceriodaphnia dubia in short-term test. The results suggest that metals such as barium, manganese and strontiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It contains a high concentration of toxic recalcitrant substances originating from the composition of the refining crude oil and hence a serious cause of pollution to the receiving environmental ecosystem (Pal, et al 2016). Studies have shown that the pollutants that are most responsible for living tissue toxicity are; ammonia, Sulfide, cyanide, phenols and hydrocarbons (Daflon, 2015). The contaminants are usually toxic and a major threat to the environment and human health due to their solubility and long accumulation period in living tissues and environmental substrates (Rahi, et al (2021; Al-Khalid and El-Naas, 2018;) For example, compounds like phenols which is highly soluble in water can be detected from few concentrations up to 7000 mg/L from a PRWW composition.…”
Section: Introductionmentioning
confidence: 99%
“…It contains a high concentration of toxic recalcitrant substances originating from the composition of the refining crude oil and hence a serious cause of pollution to the receiving environmental ecosystem (Pal, et al 2016). Studies have shown that the pollutants that are most responsible for living tissue toxicity are; ammonia, Sulfide, cyanide, phenols and hydrocarbons (Daflon, 2015). The contaminants are usually toxic and a major threat to the environment and human health due to their solubility and long accumulation period in living tissues and environmental substrates (Rahi, et al (2021; Al-Khalid and El-Naas, 2018;) For example, compounds like phenols which is highly soluble in water can be detected from few concentrations up to 7000 mg/L from a PRWW composition.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during the petroleum refining process, raw crude oil is converted into various useful end products such as gasoline, diesel fuel, kerosene, and fuel oils. Purification of crude oil utilizes huge volumes of water which causes the generation of wastewater enriched with toxic organic compounds [2,3]. Treatment of such wastewater is very essential to achieve safe environmental water quality standards before discharge into any water body [4,5].…”
Section: Introductionmentioning
confidence: 99%